2022
DOI: 10.1002/zamm.202000299
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic nonlinear free vibration of an annular plate under a nonuniform magnetic field of the long straight current‐carrying wire

Abstract: In this article, the magnetoelastic nonlinear free vibration of a thin conductive annular plate under the nonuniform toroidal magnetic field is investigated, where the magnetic field is generated by a long straight current-carrying wire.Based on electromagnetic theory, expressions of the nonuniform magnetic field, electromagnetic forces are deduced. The nonlinear free vibration equation of plate is derived by using the Hamilton principle. Considering different boundary conditions, the axisymmetric vibration di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The account of nonlinearity in magnetoelasticity usually is limited by the nonlinearity of the interaction between the elastic medium and the electromagnetic field [18,19] and the nonlinearity associated with thermal stresses [20].…”
Section: Introductionmentioning
confidence: 99%
“…The account of nonlinearity in magnetoelasticity usually is limited by the nonlinearity of the interaction between the elastic medium and the electromagnetic field [18,19] and the nonlinearity associated with thermal stresses [20].…”
Section: Introductionmentioning
confidence: 99%
“…They nally obtained an analytical secondapproximation solution using multiple scales followed by the expressions for the rst three nondimensional natural frequencies of the plate. Xu et al [21] studied the magnetoelastic nonlinear free vibration of thin conductive annular plates under a nonuniform magnetic eld generated by a long wire carrying current. Their results indicated that with an increase in the current, the natural frequency would be notably enhanced and then stabilized in the inner-clamped and out-clamped boundaries; however, it would be reduced and stabilized in the inner-simple and out-simple boundaries.…”
Section: Introductionmentioning
confidence: 99%